2008
DOI: 10.14227/dt150208p7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Dialysis and Dispersion Methods for In Vitro Release Determination of Drugs from Multilamellar Liposomes

Abstract: The aim of these studies was to compare dialysis and dispersion methods for determining in vitro release of propranolol, metoprolol, pindolol, and atenolol from multilamellar liposomes. Multilamellar vesicles (MLV) were prepared using hydrogenated soy-lecithin phospholipon 90H (Ph 90H) as the primary lipid. The same volume of pH 7.4 phosphate buffered saline was used as a receptor medium for both methods. Samples were withdrawn, and drug concentration was determined using HPLC. All drug-containing liposomes ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 8 publications
0
14
0
1
Order By: Relevance
“…3A illustrates two examples, ideal one for the case when the carrier retains the drug during the transport in the blood compartments and the tumor tissue, but releases it in the tumor cells, and the other for a typical case of undesirable burst release when the carrier releases its drug cargo prematurely while still circulating in the blood. Such a burst release is generally observed for polymer particles [9][10][11] and liposomes [12,13]. As a result, the drug is dumped in the blood compartments, which causes not only local or systemic toxicity, but also lowers drug availability to the tumor and thereby therapeutic efficacy.…”
Section: The 2r2s Capability Of Nanocarriersmentioning
confidence: 97%
“…3A illustrates two examples, ideal one for the case when the carrier retains the drug during the transport in the blood compartments and the tumor tissue, but releases it in the tumor cells, and the other for a typical case of undesirable burst release when the carrier releases its drug cargo prematurely while still circulating in the blood. Such a burst release is generally observed for polymer particles [9][10][11] and liposomes [12,13]. As a result, the drug is dumped in the blood compartments, which causes not only local or systemic toxicity, but also lowers drug availability to the tumor and thereby therapeutic efficacy.…”
Section: The 2r2s Capability Of Nanocarriersmentioning
confidence: 97%
“…At predetermined time intervals; 2 ml aliquots of the release medium was sampled and replaced with 2 ml fresh Eth-HS solution. The samples were suitably diluted with Eth-HS solution and the drug concentration was measured spectrophotometry at λR maxR of 238 nm [20]. Drug concentration was determined using the previously prepared standard curve of BD in Eth-HS solution and all experiments were conducted in triplicates.…”
Section: In Vitro Drug Release Studymentioning
confidence: 99%
“…The shear stress in dyne/cmP 2 P and the viscosity in centipose were determined at a different shear rate (2,6,10,20,24,60, 100 and 120 secP -1 P ) using spindle number 52.…”
Section: Rheological Studymentioning
confidence: 99%
“…1,2 Phospholipids have therefore been used to prepare biomimetic capsular structures (mainly liposomes or micelles), [3][4][5][6] films, coatings for water microdroplets, 2 and microbubbles 7 with a broad range of applications, including drug delivery, 8 cell encapsulation, 9 and tissue engineering. McKee and co-authors 10,11 have shown that a solution of phospholipids above 35% w/w in DMF:CHCl3 [3:2 v/v] is capable of forming continuous fibers using electrospinning processing with an average phospholipid fiber diameter of $3.3 lm (for 45% w/w solution).…”
Section: Nanomechanics Of Electrospun Phospholipid Fibermentioning
confidence: 99%